SCIENTIFIC-THEORETICAL BASIS OF COORDINATION OF EDUCATIONAL METHODS (Academia Science Repository, 2023)
In this article, the new demands placed on the content of education are to provide the young generation with high scientific and theoretical knowledge, in particular, on the basics of science, and this work describes the classification of theoretical and practical knowledge methods and new interactive methods information is provided.